Modeling Crisis Evolution and Counterfactual Policy Simulations: A Country Case Study - Iwan J. Azis (Asian Development Bank Institute (ADBI), 2001)
This study is using the case of one country, i.e., Indonesia. It describes how that country'seconomic policies evolved and why some of them may have planted the seeds for the subsequent crisis.The paper also discusses the dynamics and sequence of events that took place during the episode. Themechanisms of the process are explained using a comprehensive financial sector general equilibriummodel, in order to help one better understand how various variables and indicators interacted duringthe crisis. In the benchmark run, the values of all exogenous variables (including policy variables) andexogenous events that precipitated the crisis are set equal to their actual (observed) values, and themodel is used to derive the resulting values of the endogenous variables. The results of the simulationclosely replicate the changes and trends that actually occurred.
hdl:11540/4128
Keywords: 330